The Effect of Giving Green Apple (Malus Domestica) Juice on the Histopathology of White Rat Pulmonary Organs Induced by Cigarette Smoke - Pranata, Chandra; Asti Pratiwi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Cigarette smoke contains oxidants or free radicals and around 4700 dangerous chemicals. The high level of free radicals in the body triggers the emergence of Reactive Oxygen Species (ROS) which results in oxidative stress, this can occur if there is an imbalance between the amount of oxidants and antioxidants. In this process, there is a leak of O2 which will turn into superoxide radicals (*O2) which can form pro-inflammatory cytokines such as IL-6. Objective: to identify the effect of exposure to cigarette smoke on the histopathological appearance of rat lungs. Method: This research uses Post Test Only Control Group Design. Samples were taken from 20 male rats that met the inclusion criteria and were randomly divided into 4 groups, namely K1, K2, K3, and K4. K3 was given standard feed plus green apple juice at a dose of 13.5 grams/day. Meanwhile, the K4 group was given standard feed plus green apple juice at a dose of 27 grams/day. However, both were given exposure to cigarette smoke for 14 days. On the 15th day, blood was taken from male Wistar rats to carry out a histopathological examination of the rats' lungs using Hematoxillin-Eosin staining. Results: The results showed that there was damage in the negative group when compared with the normal group and the highest improvement in lung tissue was found at a dose of 27 grams/day when compared with the negative and normal groups. Conclusion: There is an effect of giving green apple juice on IL-6 and SOD levels in mice exposed to cigarette smoke.